PENGARUH STRATEGI PEMASARAN TERHADAP KEPUASAN DAN KEPUTUSAN PEMBELIAN PRODUK USAHA KECIL MENENGAH (UKM) 310 DI MAKASSAR - Nur Naninsih; Hardiyono Hardiyono (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2019)
This study aims to determine the effect of marketing strategies on satisfaction and purchasing decisions for small and medium enterprises (UKM) 310 in Makassar. This research uses quantitative research. Quantitative research is a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know. The results of this study found that partially marketing strategies have a positive and significant effect on buyer satisfaction, marketing strategies have a positive and significant effect on purchasing decisions, and satisfaction has a positive and significant effect on purchasing decisions. The indirect influence shows that marketing strategies have a positive and significant effect on purchasing decisions through satisfaction.